2020
DOI: 10.1186/s12885-020-6649-2
|View full text |Cite
|
Sign up to set email alerts
|

Unphosphorylated STAT3 in heterochromatin formation and tumor suppression in lung cancer

Abstract: Background: Aberrant JAK/STAT activation has been detected in many types of human cancers. The role of JAK/ STAT activation in cancer has been mostly attributed to direct transcriptional regulation of target genes by phosphorylated STAT (pSTAT), while the unphosphorylated STAT (uSTAT) is believed to be dormant and reside in the cytoplasm. However, several studies have shown that uSTATs can be found in the nucleus. In addition, it has been shown that tissue-specific loss of STAT3 or STAT5 in mice promotes cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…It was demonstrated that a JAK downstream transcription factor, the signal‐transducer and activator of transcription protein at 92E (Stat92E), in its unphosphorylated form, interacts with HP1a, promoted heterochromatin formation, 92,96,97 and enhanced genome stability 98 ; moreover, this interaction was also found to protect against leukemia‐like cancer formation 92 . A similar mechanism was also demonstrated in mammals to suppress cancer development, 99,100 highlighting the advantage of using Drosophila for discovering conserved mechanisms.…”
Section: Epigenetic Mechanisms Implicated In Drosophila and Human Agingmentioning
confidence: 87%
See 1 more Smart Citation
“…It was demonstrated that a JAK downstream transcription factor, the signal‐transducer and activator of transcription protein at 92E (Stat92E), in its unphosphorylated form, interacts with HP1a, promoted heterochromatin formation, 92,96,97 and enhanced genome stability 98 ; moreover, this interaction was also found to protect against leukemia‐like cancer formation 92 . A similar mechanism was also demonstrated in mammals to suppress cancer development, 99,100 highlighting the advantage of using Drosophila for discovering conserved mechanisms.…”
Section: Epigenetic Mechanisms Implicated In Drosophila and Human Agingmentioning
confidence: 87%
“…• Reduced expression of NuRD components in Hutchinson-Gilford progeria syndrome (HGPS, OMIM 176670), HGPS-derived cells and those from older donors • Reduced HDAC1 activity (encoded by Hsa-HDAC1) was also found (the NuRD chromatin remodeling complex that includes HDAC1 and HDAC2), suggesting that the mechanism could also be related to histone acetylation [296] mechanism was also demonstrated in mammals to suppress cancer development, 99,100 highlighting the advantage of using Drosophila for discovering conserved mechanisms.…”
Section: Drosophilamentioning
confidence: 99%
“…To identify potential mechanisms by which senescent cells impact on alveolar epithelial cells modulation of known SASP factors such as IL-6, IL-1β, PDGF, FGFb, PGE 2 and ROS would be the focus of future studies [41,42]. Interestingly, STAT3 has been reported to be involved in fibroblast senescence but a recent publication has highlighted the potential involvement in epithelial cell senescence [43]. This is the first study to show that senescent LFs are able to reduce alveolar epithelial cell proliferation in a co-culture system.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, not only has STAT3 been linked to fibrosis in the liver but it is also an important regulator in a model of oxidative stress-induced senescence in primary human lung fibroblasts [ 41 ]. Recently, it was suggested that STAT3 potentially is involved in epithelial cell senescence [ 106 ]. In addition to regulation by TGF-β, it was concluded that matrix stiffness has a substantial impact on the intrinsic and extrinsic activation of the STAT3 pathway in hepatocellular carcinoma cells [ 107 ].…”
Section: The Ecm–cell Interactions That Potentially Drive Cellular Sementioning
confidence: 99%